La evolución del sistema de partidos de Galicia - Nieves Lagares Diez (Cahiers de Civilisation Espagnole Contemporaine)
With the approval of the 1980 Statute of Autonomy, Galicia began the process of building its own autonomous political system. The aim of this paper is to analyse the evolution of the Galician party system by identifying the different stages, the functioning of the competition between parties, the relationship between the political strategies of these parties and the formation of the preferences of the voters. In this analytical journey, we point out five periods that correspond to electoral cycles of vote dispersion and concentration, depending on the dynamics of political competition and the governments that result from them. What the evolution of the Galician party system shows is the definition of certain original characteristics that provide stability to the functioning of competition within the system.